(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article devotes to semantic and functional characteristics of aspect as grammatical category (on a material of the Ukrainian and foreign researches). Multifaceted semantic of perfective and imperfective aspect is also described in the work.